India´'s Place in the Foreign Policy of Brazil: the multilateral nexus - Santoro Rocha, Mauricio (Faculdade de Filosofia e Ciências, 2020)
Cooperation between Brazil and India in multilateral organizations goes back to the 1960s, with common positions in several United Nations´ agencies and in GATT. In the current period, post-Cold War, it has been the strongest characteristic of the relation among both countries, with partnerships in many global forums, such as BRICS, G4, G20, BASIC, IBSA, with common goals of reform the international system attending the demands of emerging nations. This affinity creates possibilities for Brazilian foreign policy regarding an Asia on the rise, including the opportunity for some balancing for the growing influence of China.